2022
DOI: 10.3831/kpi.2022.25.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bloodletting and Cupping in Severe Acute Urticaria and Angioedema as Skin Emergencies in Persian Medicine

Abstract: Objectives Some dermatological diseases can be life-threatening. Urticaria and angioedema are common reasons for patients to seek treatment at an emergency department. Severe, generalized urticaria and angioedema can endanger patients’ lives by involving the airways and causing anaphylactic shock. The humor-based Persian Medicine (PM) concepts of Shara and Mashara , referring to two kinds of skin lesions, have similarities to urticaria and angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
(65 reference statements)
0
0
0
Order By: Relevance
“…However, our study participants showed limited awareness of the efficacy of CT in treating dermatological conditions such as urticaria which is reported in the literature. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, our study participants showed limited awareness of the efficacy of CT in treating dermatological conditions such as urticaria which is reported in the literature. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%